Some application of difference equations in Cryptography and Coding Theory - Flaut, Cristina (Journal of difference equations and applications, 2019)
In this paper, we present some applications of a difference equation of degree k. Using such an equation, we provide an algorithm for messages encryption and decryption. Moreover, by using the matrix associated to a difference equation of degree k, we present an application in Coding Theory.